Can Student Learning Engagement Strengthen The Link Between Deep Learning Approach And Perceived Learning? - David Sukardi Kodrat; Benny Irawan; Elsima Nainggolan (Lembaga Penelitian dan Pengabdian Masyarakat IAIN Kediri, 2026)
This study sought to explore how engagement-oriented learning processes support students’ more profound understanding and sustained knowledge retention, thereby offering contributions to both educational theory and practice. A quantitative approach was applied to examine the determinants of perceived learning. The study encompassed 386 students selected from a total population of 7,261 students. Data analysis was carried out using Structural Equation Modeling (SEM) with a Partial Least Squares (PLS) technique to investigate the relationships among three latent constructs: deep learning approach, student learning engagement, and perceived learning. The findings revealed that the deep learning approach significantly influenced perceived learning and had a substantial effect on student learning engagement. Additionally, student learning engagement was found to affect perceived learning significantly. With regard to indirect effects, the results showed that the deep learning approach affected perceived learning through student learning engagement. These results indicate that deep learning strategies not only directly enhance perceived learning but also indirectly strengthen it by promoting higher levels of student engagement, highlighting the mediating role of student learning engagement.